Scaki - The scaffolding wiki - Fernández, Alejandro (^p Datos electrónicos (1 archivo : 280 KB))
Support for documenting and managing work processes is valuable for any distributed software development team. Existing tools for process documentation and enactment are complex and expensive. Scaffolding is a simple approach to describe practices. WikiWikiWeb is a simple and inexpensive collaborative publication tool. This paper proposes extensions to exploit the simplicity of WikiWikiWeb to create and tailor scaffoldings of work processes that can be enacted.